The costs of and economies of scale in supporting students from low socioeconomic status backgrounds in Australian higher education - Devlin, Marcia; Zhang, Liang-Cheng; Edwards, Daniel; Withers, Glenn; McMillan, Julie; Vernon, Lynette; Trinidad, Sue (Higher education research and development, 2023)
This study examined the costs of supporting Australian university students from different socioeconomic status (SES) backgrounds and whether there are economies of scale. The mixed-methods research in 2018 and 2019 found that substantially higher costs applied for supporting students from low SES backgrounds. These were explained by the costs inherent in: increasing aspiration and capital prior to university; academic, personal and financial support provided while studying; establishing, maintaining and appropriately staffing multiple university campuses, particularly in highly disadvantaged areas; and supporting highly complex student needs. It was found that there are significant economies of scale where there are between 517 and 2584 fulltime undergraduate students from low SES backgrounds at a university. It follows that the average cost of supporting these students can be reduced if enrolment numbers are within this range, subject to caveats around the costs identified. Potential policy implications include: a redistribution of funding based on need; shifting emphasis from activity-based to mission-directed costing; applying the principles of 'cost compensation'; and conceptualising funding support for students from low SES backgrounds as a transformational investment that can improve outcomes for individuals, communities and society, rather than as a cost.